Recurrent IgA nephropathy after renal transplantation and steroid withdrawal. Issue 4 (20th February 2018) - Di Vico, Maria Cristina; Messina, Maria; Fop, Fabrizio; Barreca, Antonella; Segoloni, Giuseppe Paolo; Biancone, Luigi
Abstract: Immunoglobulin A nephropathy (IgAN) is the most common primary glomerulonephritis; the reported recurrence rate of IgAN after renal transplantation is as high as 13%‐50%. The impact of immunosuppressive therapy and steroid withdrawal on the risk of recurrence of IgAN is still under debate. We performed a retrospective single‐center study, selecting 123 kidney transplants (rtx) in 120 patients, between January 1995 and December 2012, with IgAN on the native kidney. In 51 of 123 transplants, at least one post‐transplantation biopsy for clinical indication was performed; in 28 of 51 transplants, IgAN recurrence (IgANr) was demonstrated. This group (G1; N = 28) was compared with a group without IgANr (G2; N = 23). In our study, clinically evident IgANr rate was 54.9% (28/51) on biopsied patients. At discharge, the use of the immunosuppressant drugs (tacrolimus, cyclosporine A, mycophenolate mofetil, azathioprine, mTor inhibitors) was not associated with an increased risk of IgANr ( P = NS). At discharge, all patients were steroid treated. Neither the use of tacrolimus, mycophenolate mofetil, nor mTor inhibitors (mTori) at biopsy time were associated with IgANr. However, IgANr was significantly higher in patients who experienced steroid withdrawal at any post‐transplantation time (OR 7.7 P = .03). The median time to recurrence after steroid withdrawal was 59 months (min 4.18, max 113.2).